Connexins in oligodendrocytes and astrocytes: Possible factors for demyelination in multiple sclerosis. (June 2020) - Xia, Cong-Yuan; Xu, Jie-Kun; Pan, Chen-Hao; Lian, Wen-Wen; Yan, Yu; Ma, Bing-Zhi; He, Jun; Zhang, Wei-Ku
Abstract: Increasing evidences support that glial connexins are involved in the demyelination pathology of multiple sclerosis (MS), a chronic inflammatory demyelinating disorder. Here, we review the data from patients with MS and animal models of MS that implicate connexins in demyelination. Connexins expressed in oligodendrocytes and astrocytes show diverse changes at the different phases of MS. Loss of oligodendrocyte or astrocyte connexins contributes to demyelination and exaggerates the pathology of MS. Channel-dependent and –independent connexins are involved in the pathology of demyelination, which is related with myelin integrity, metabolic homeostasis, the brain-blood barrier, the immune cell infiltration, and the inflammatory response. A comprehensive understanding of connexin function in demyelination may provide new therapeutic targets for MS. Highlights: Connexins in oligodendrocytes and astrocytes play an essential role in the development and maintenance of myelin. The function of connexins in oligodendrocytes and astrocytes is important in MS pathology. Role of connexins in demyelination phase may provide novel therapeutic targets for MS.